BRAND EXPERIENCE IMPACT ON BRAND LOYALTY AT FIT HUB SURABAYA MEDIATED BY PERCEIVED QUALITY AND BRAND TRUST - Lena Ellitan; Marcell Valentino (Research In Management and Accounting (RIMA), 2026)
This study aims to examine the effect of brand experience on brand loyalty mediated by perceived quality and brand trust at Fit Hub. The increasing number of awareness of the importance of health and modern lifestyles today has created great opportunities for the fitness industry. One of the innovations in this industry sector is Fit Hub, a business concept that combines a modern fitness center with services that can help meet diverse consumer needs. This research uses causal research. The sampling technique for this research is nonprobability sampling with purposive sampling. The sample in this study amounted to 178 respondents. The data collection tool used is a questionnaire. The data collection tool used is a questionnaire. The data analysis technique used is Structural Equation Modeling using the Smart PLS 4.0 program. The results of this study indicate that brand experience has a positive and significant effect on brand loyalty, brand experience has a positive and significant effect on perceived quality, brand experience has a positive and significant effect on brand trust, perceived quality has a positive and significant effect on brand loyalty, brand trust has an insignificant effect on brand loyalty, perceived quality has a positive and significant effect on mediating the effect of brand engagement on brand loyalty, brand trust has an insignificant effect on mediating the effect of brand engagement on brand loyalty.